Korzystny wpływ kwasów omega-3 na rozwój dziecka = The beneficial effect of omega-3 acids on child development - Pluta, Agnieszka; Budnik-Szymoniuk, Maria (Journal of Education, Health and Sport, 2016)
Pluta Agnieszka, Budnik-Szymoniuk Maria. Journal of Education, Health and Sport. 2016;6(7):540-547. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58956 http://ojs.ukw.edu.pl/index.php/johs/article/view/3718 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. Korzystny wpływ kwasów omega-3 na rozwój dziecka The beneficial effect of omega-3 acids on child development Agnieszka Pluta, Maria Budnik-Szymoniuk Department of Community Nursing Faculty of Health Sciences Collegium Medicum in Bydgoszcz of the Nicolaus Copernicus University in Toruń Zakład Pielęgniarstwa Społecznego Collegium Medicum w Bydgoszczy Uniwersytetu Mikołaja Kopernika w Toruniu Keywords: child development, omega-3acids, supplementation. Słowa kluczowe: rozwój dziecka, kwasy omega-3, suplementacja. Abstract Fatty acids are one of the determinants of normal development of the child. A special role is attributed to omega-3 acids. Representative of this group of acids include alpha-linolenic acid, eicosapentaenoic acid and docosahexaenoic acid. The paper presents the biological activity of omega-3 with a particular focus on their impact on child development. Streszczenie Kwasy tłuszczowe są jednym z determinantów prawidłowego rozwoju dziecka. Szczególną rolę przypisuje się kwasom omega-3. Przedstawicielami tej grupy kwasów są kwas alfa-linolenowy, dokozaheksaenowy oraz eikozapentaenowy. W pracy przedstawiono aktywność biologiczną kwasów omega-3 ze szczególnym uwzględnieniem ich wpływu na rozwój dziecka.